Keratoconus Diagnosis with Optical Coherence Tomography Pachymetry Mapping - Li, Yan (2008)
OBJECTIVE: To detect abnormal corneal thinning in keratoconus using pachymetry maps measured by high-speed anterior segment optical coherence tomography (OCT). DESIGN: Cross-sectional observational study. PARTICIPANTS: Thirty-seven keratoconic eyes from 21 subjects and 36 eyes from 18 normal subjects. METHODS: The OCT system operated at a 1.3 μm wavelength with a scan rate of 2000 axial scans per second. A pachymetry scan pattern (8 radials, 128 axial scans each; 10 mm diameter) centered at the corneal vertex was used to map the corneal thickness. The pachymetry map was divided into zones by octants and annular rings. Five pachymetric parameters were calculated from the region inside the 5 mm diameter: minimum, minimum–median, inferior–superior (I-S), inferotemporal–superonasal (IT-SN), and the vertical location of the thinnest cornea. The 1-percentile value of the normal group was used to define the diagnostic cutoff. Placido-ring–based corneal topography was obtained for comparison. MAIN OUTCOME MEASURES: The OCT pachymetric parameters and a quantitative topographic keratoconus index (keratometry, I-S, astigmatism, and skew percentage [KISA%]) were used for keratoconus diagnosis. Diagnostic performance was assessed by the area under the receiver operating characteristic (AROC) curve. RESULTS: Keratoconic corneas were thinner. The pachymetric minimum averaged 452.6±60.9 μm in keratoconic eyes versus 546±23.7 μm in normal eyes. The 1-percentile cutoff was 491.6 μm. The thinnest location was inferiorly displaced in keratoconus (−805±749 μm vs −118±260 μm ; cutoff, −716 μm). The thinning was focal (minimum–median: −95.2±41.1 μm vs −45±7.7 μm ; cutoff, −62.6 μm). Keratoconic maps were more asymmetric (I-S, −44.8±28.7 μm vs −9.9±9.3 μm ; cutoff, −31.3 μm ; and IT-SN, −63±35.7 μm vs −22±11.4 μm ; cutoff, −48.2 μm). Keratoconic eyes had a higher KISA% index (2641±5024 vs 21±19). All differences were statistically significant (t test, P<0.0001). Applying the diagnostic criteria of any 1 OCT pachymetric parameter below the keratoconus cutoff yielded an AROC of 0.99, which was marginally better (P= .09) than the KISA% topographic index (AROC, 0.91). CONCLUSIONS: Optical coherence tomography pachymetry maps accurately detected the characteristic abnormal corneal thinning in keratoconic eyes. This method was at least as sensitive and specific as the topographic KISA. FINANCIAL DISCLOSURE(S): Proprietary or commercial disclosure may be found after the references.